Prenatal and postnatal exposure to organophosphate pesticides and childhood neurodevelopment in Shandong, China. (November 2017) - Wang, Yiwen; Zhang, Yan; Ji, Lin; Hu, Yi; Zhang, Jingjing; Wang, Caifeng; Ding, Guodong; Chen, Limei; Kamijima, Michihiro; Ueyama, Jun; Gao, Yu; Tian, Ying
Abstract: Background: Although studies in laboratory animals demonstrate neurodevelopmental deficits caused by prenatal or postnatal organophosphate pesticide (OP) exposure, there is limited evidence on effects induced by not only prenatal but also postnatal exposure of children to OPs. Methods: We measured diethylphosphate (DE), dimethylphosphate (DM), and total dialkylphosphate (DAP) metabolites in maternal and child urine at 12 and 24 months of age and examined their relationship with developmental quotients (DQs) in 12-month-old infants and 24-month-old children in Shandong, China. Results: The median concentrations of total DAP metabolites (DAPs) in child urine [371.97 nmol/g creatinine (12-month-old infants), 538.64 nmol/g creatinine (24-month-old children)] were higher than those in maternal urine (352.67 nmol/g creatinine). Prenatal OP exposure was negatively associated with 24-month-old children's DQs, especially among boys. A 10-fold increase in prenatal DEs and DAPs was associated with a 2.59- and 2.49-point decrease in social domain DQ scores in 24-month-old children ( n  = 262), respectively. However, positive association of postnatal exposure to OPs and 24-month-old children's DQs was observed ( n  = 237). Neither prenatal nor postnatal exposure to OPs was related to 12-month-old infants' DQs. Conclusions: These data suggested that prenatal OP exposure could adversely affect children's neurodevelopment at 24 months of age, especially among boys. The prenatal period might be a critical window of OP exposure. In view of the positive association with postnatal OP exposure, it is necessary to interpret findings with caution. Highlights: The DAP concentrations in child urine were higher than those in maternal urine. Prenatal OP exposure was negatively associated with 24-month-old children's DQs. Postnatal OP exposure was positively associated with 24-month-old children's DQs. The prenatal period might be a critical window of OP exposure.